Social media, professional understanding and professional identities amongst Vietnamese ESOL teachers (Revista Lusófona de Educação, 2026)
Vietnam is one of the world’s fastest-growing economies, and English proficiency has been acknowledged as crucial to Vietnam’s development, leading to the implementation of the National Foreign Languages 2020 project. However, despite the emphasis placed on the professional development of teachers in Vietnam, the effectiveness of centralized and school-level professional development programmes has been questioned. Parallel to these formal structures, groups created on social media platforms have gained popularity among educators in Vietnam. The educators who engage with and create these communities demonstrate autonomy and agency over their own development. Previous research has highlighted the positive impact of social media-based communities of practice on teachers' professional growth, but little is known about their specific effect in Vietnam or in emerging economies more broadly, nor has the inter-generational conversation facilitated by such communities been previously explored. This study takes one step in furthering our understanding within this important context by examining the role of autonomously created social media communities for professional development among Vietnamese ESOL teachers. It revealed that teachers valued these virtual communities for enhancing knowledge, networking, job opportunities, research ideas, and mental health support, and also that membership positively shaped their professional identity. These findings suggest that social media can effectively support teachers' development, and while such communities could pose a challenge for mainstream, formally created communities, policymakers should encourage their use for professional development. As one of the world’s fastest-growing economies, research into the Vietnamese context also has deeper relevance as a window into global change.Keywords: communities of practice, social media, teachers’ professional knowledge, teachers’ professional identities, Vietnamese teachers of English.